Increased Blood Pressure Variability Prior to Chronic Kidney Disease Exacerbates Renal Dysfunction in Rats - Freitas, Frederico F. C. T.; Araujo, Gilberto; Porto, Marcella L.; Freitas, Flavia P. S.; Graceli, Jones B.; Balarini, Camille M.; Vasquez, Elisardo C.; Meyrelles, Silvana S.; Gava, Agata L. (Frontiers in Physiology, 2016)
Increased blood pressure variability (BPV), which can be experimentally induced by sinoaortic denervation (SAD), has emerged as a new marker of the prognosis of cardiovascular and renal outcomes. Considering that increased BPV can lead to organ-damage, the goal of the present study was to evaluate the effects of SAD on renal function in an experimental model of chronic kidney disease (CKD). SAD was performed in male Wistar rats 2 weeks before 5/6 nephrectomy and the animals were evaluated 4 weeks after the induction of CKD. Our data demonstrated that BPV was increased in SAD and CKD animals and that the combination of both conditions (SAD+CKD) exacerbated BPV. The baroreflex sensitivity index was diminished in the SAD and CKD groups; this reduction was more pronounced when SAD and CKD were performed together. 5/6 nephrectomy led to hypertension, which was higher in SAD+CKD animals. Regarding renal function, the combination of SAD and CKD resulted in reduced renal plasma and blood flow, increased renal vascular resistance and augmented uraemia when compared to CKD animals. Glomerular filtration rate and BPV were negatively correlated in SAD, CKD and SAD+CKD animals. Moreover, SAD+CKD animals presented a higher level of glomerulosclerosis when compared to all other groups. Cardiac and renal hypertrophy, as well as oxidative stress, was also further increased when SAD and CKD were combined. These results show that SAD prior to 5/6 nephrectomy exacerbates renal dysfunction, suggesting that previous augmented BPV should be considered as an important factor to the progression of renal diseases.